The flexibility of two tropomyosin mutants, D175N and E180G, that cause hypertrophic cardiomyopathy - Li, Xiaochuan (Edward); Fischer, Stefan (Biochemical and biophysical research communications, 2012)
Point mutations targeting muscle thin filament proteins are the cause of a number of cardiomyopathies. In many cases, biological effects of the mutations are well-documented, whereas their structural and mechanical impact on filament assembly and regulatory function is lacking. In order to elucidate molecular defects leading to cardiac dysfunction, we have examined the structural mechanics of two tropomyosin mutants, E180G and D175N, which are associated with hypertrophic cardiomyopathy (HCM). Tropomyosin is an α-helical coiled-coil dimer which polymerizes end-to-end to create an elongated superhelix that wraps around F-actin filaments of muscle and non-muscle cells, thus modulating the binding of other actin-binding proteins. Here, we study how flexibility changes in the E180G and D175N mutants might affect tropomyosin binding and regulatory motion on F-actin. Electron microscopy and Molecular Dynamics simulations show that E180G and D175N mutations cause an increase in bending flexibility of tropomyosin both locally and globally. This excess flexibility is likely to increase accessibility of the myosin-binding sites on F-actin, thus destabilizing the low-Ca2+ relaxed-state of cardiac muscle. The resulting imbalance in the on-off switching mechanism of the mutants will shift the regulatory equilibrium towards Ca2+-activation of cardiac muscle, as is observed in affected muscle, accompanied by enhanced systolic activity, diastolic dysfunction, and cardiac compensations associated with HCM and heart failure.
Gesehen am 09.11.2018